Students’ Problems in Learning Conjunction - Syamsul Bahri Panggabean (VISION, 2016)
This paper is discussed about students’ problems in learning conjunction. Conjunction is one of the topic in part of speech that should be learnt by the students. The srtudents faced problems in identifying the types of conjunction and how to use it in sentence.